PENGARUH PEMBERIAN KOMBINASI METFORMIN DENGAN EKSTRAK KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) TERHADAP KADAR GLUKOSA DARAH MENCIT DIABETES - Khotimah, Khusnul; Kadir, Mujtahid Bin Abd; Kasimo, Elfred Rinaldo; Sanjaya, Rochmad Kris (Universitas Kadiri, 2021)
People with diabetes mellitus extremely increase every year. Management of diabetes mellitus disease requires appropriate therapy to prevent serious increasing and progressing the disease to be serious complication then the achievement of therapy goals. This study aims to determine the effect of giving a combination of metformin and red dragon fruit peel extract (Hylocereus polyrhizus) on blood glucose levels of diabetic mice.This type of research is an experimental study with a pre-test and post-test design with a control group. As the test animal, Swiss webster male white mice were used. They were grouped into 6 groups, each with 4 tails for each group. As the treatment group by giving of a combination of metformin and red dragon fruit peel extract with various doses of 75 mg/kg body weight for mice, 150 mg/kg body weight for mice, 300 mg/kg body weight for mice, positive control for metformin 65 mg/kg BW for mice, comparative control extracts red dragon fruit peel 150 mg/kg BW of mice and negative control 0.5% Na CMC was given orally once a day for 14 days. Data analysis used the One Way Anova method followed by the Last Significant Difference (LSD) method.The results showed that the percentage of the highest reduction in blood glucose levels was 81% in the combination group with an extract dose of 300 mg/kg BW of mice which was significantly different from the negative control group and the comparison control group.